Body, Gender and Sexuality in Indiscipline Records - Anderson Ferrari; Marcos Adriano de Almeida (Universidade Federal do Rio Grande do Sul, 2012)
This article is the result of a research realized in the Pedagogical Actions Department in Juiz de Fora Education Secretary Office. Working with the records from 2007 to 2009, we will center our analysis in the cases in which the body, gender and sexuality interact with 'indiscipline'. Understanding these categories as discursive and historical constructions, we are purposing to think the constructions mechanisms through what is faced and happened at school. In this way, it is the Post-structuralism perspective, mainly the contributions by Michel Foucault, that will be our theoretical-methodological basis.